Ageing with joy : the effect of a physical activity programme on the well-being of older people : a study conducted in five homes for the elderly in Paramaribo - Chang, Chang Ming Sing (Graduate School for Health Research SHARE [S.l.], 2009)
Presents a study of physical activity for the elderly. Discusses the ageing global population with reflection on the situation in Suriname.